I heard God laugh : a practical guide to life's essential daily habit - Kelly, Matthew (Florida Blue sparrow, 2020)
The author uses his own spiritual journey to illustrate how tending to your soul through prayer can change your life for the better. -- Provided by publisher.
Most of us are trying to put together the jigsaw puzzle we call life without a very important piece. Over time this becomes incredibly frustrating. In this extraordinary book, Matthew Kelly powerfully demonstrates that we cannot live the life we have imagined, or experience the joy we yearn for, unless we learn to tend the soul. From there, with his classic style of practical wisdom, he teaches us how to remedy this problem. When our bodies are hungry, our stomachs growl. When our souls are hungry, we become irritable, restless, confused, overwhelmed, exhausted, anxious, discontent, and tend to focus on the things that matter least and neglect the things that matter most. Are you taking care of your soul? Are you feeding it and nurturing it? Or are you ignoring it and neglecting it? The reality is, most people have never really been taught how to tend their souls. I Heard God Laugh will help you to do just that, and so much more. If you ever wondered how Matthew Kelly has been able to write and speak the way he has over the past three decades, he is about to share his secret with you. As he shares what transformed his life, along with intimate details of his own journey and struggle, he teaches us how to apply the great spiritual lessons learned to our own lives. At every turn he floods the reader with hope and demonstrates unmistakably that the best is yet to come! -- Provided by publisher.
Part one: The unexpected life -- Part two: My spiritual journey -- Part three: Life's essential habit -- Part four: Six powerful spiritual lessons -- Part five: The God who gave us laughter -- Epilogue: Do you hear that?.
"Nothing will change your life so completely, absolutely, and forever like really learning how to pray"--Preliminary pages.
Keywords: Prayer -- Christianity; Christian life; Laughter -- Religious aspects; Christian life; Laughter -- Religious aspects; Prayer -- Christianity; Nonfiction